The Role of White Matter in the Neural Control of Swallowing: A Systematic Review - Alvar, Ann; Hahn Arkenberg, Rachel; McGowan, Bethany; Cheng, Hu; Malandraki, Georgia A. (Frontiers in Human Neuroscience, 2021)
Background: Swallowing disorders (dysphagia) can negatively impact quality of life and health. For clinicians and researchers seeking to improve outcomes for patients with dysphagia, understanding the neural control of swallowing is critical. The role of grey matter in swallowing control has been extensively documented, but knowledge is limited regarding the contributions of white matter. Our aim was to identify, evaluate, and summarize the populations, methods, and results of published articles describing the role of white matter in neural control of swallowing. Methods: We completed a systematic review with a multi-engine search following PRISMA-P 2015 standards. Two authors screened articles and completed blind full-text review and quality assessments using an adapted U.S. National Institute of Health’s Quality Assessment. The third author resolved any disagreements. Qualitative synthesis of evidence was completed. Results: The search yielded 105 non-duplicate articles, twenty-two of which met inclusion criteria. Twenty were rated as Good (5/22; 23%) or Fair (15/22; 68%) quality. Stroke was the most represented diagnosis (n=20; 91%). All studies were observational, and half were retrospective cohort design. The majority of studies (13/22; 59%) quantified white matter damage with lesion-based methods, whereas 7/22 (32%) described intrinsic characteristics of white matter using methods like fractional anisotropy. Fifteen studies (68%) used instrumental methods for swallowing evaluations. White matter areas commonly implicated in swallowing control included the pyramidal tract, internal capsule, corona radiata, superior longitudinal fasciculus, external capsule, and corpus callosum. Additional noteworthy themes included: severity of white matter damage is related to dysphagia severity; bilateral white matter lesions appear particularly disruptive to swallowing; and white matter adaptation can facilitate dysphagia recovery. Gaps in the literature included limited sample size and populations, lack of in-depth evaluations, and issues with research design. Conclusion: Although traditionally understudied, there is sufficient evidence to conclude that white matter is critical in the neural control of swallowing. The reviewed studies indicated that white matter damage can be directly tied to swallowing deficits, and several white matter structures were implicated across studies. Further well-designed interdisciplinary research is needed to understand white matter’s role in neural control of normal swallowing and in dysphagia recovery and rehabilitation.